Quantifying population and clone-specific non-linear reaction norms to food gradients in Daphnia magna - Plaistow, Stewart J.; Brunner, Franziska S.; O’Connor, Michael (Frontiers in Ecology and Evolution, 2022)
Phenotypic plasticity is normally quantified as a reaction norm which details how trait expression changes across an environmental gradient. Reaction norms are often assumed to be linear for simplicity’s sake, but also because plasticity is typically quantified as the difference in trait expression measured in two environments. This simplification limits how plastic responses vary between genotypes and may also bias the predictions of models investigating how plasticity influences a population’s ability to adapt to a changing environment. Consequently, there is a pressing need to characterize the real shape of reaction norms and their genetic variability across ecologically relevant environmental gradients. To address this knowledge gap we measured the multi-trait plastic response of 7 Daphnia magna clones from the same population across a broad resource gradient. We used a Random Regression Mixed Model approach to characterize and quantify average and clone-specific responses to resource variation. Our results demonstrate that non-linear models outperformed a linear model for all 4 of the life-history traits we measured. The plastic reaction norms of all 4 traits were similar in shape and were often best described by a non-linear asymptotic model. Clonal variation in non-linear plastic responses was detectable for 3 out of the 4 traits that we measured although the nature and magnitude of variation across the resource gradient was trait-specific. We interpret our findings with respect to the impact that plasticity has on the evolutionary potential of a population in different resource environments.